IMPROVING NUTRITIONAL AND QUALITATIVE PROPERTIES OF WHEAT BREAD BY USING MALLOW (MALVA NEGLECTA L.) LEAVES POWDER - Ezuldeen K. Hammoud; Ahmed C. Saddam (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was investigates the effect of adding different concentrations (1, 2, 3, 4, 5, 6, 7, 8) % of mallow (Malva neglecta L.) leaves powder (MLP) to wheat bread mix on nutritional and qualitative properties of the obtained bread. Results of the chemical composition based by dry matter, moisture, ash, protein, fat, and carbohydrates for wheat flour and mallow leaves powder were 87.4, 12.6, 0.65, 10.5, 1.25, 75% and 96.2, 3.8, 7.90, 12.70, 1.60, 74.20 %, respectively. The study included nine treatments (T1, T2, T3, T4, T5, T6, T7, T8, T9 ), where T1 was the control treatment. During the fermentation period, dough mass was increased to its maximum value, T1 recorded the lowest height. The addition of (MLP) led to a slight increase in the specific volume of (T2, T3, T4, T5, T6), and this may be due to the increase in the proportion of polysaccharides in the mallow plant, while the specific volume began to decrease significantly in treatments (T7, T8, T9). Each of (T7, T8, and T9) showed significant differences as compared with the control treatment (T1) for the characteristics of color of crust, symmetry of form, evenness of bake, grain, color, texture of crumb, aroma, and taste. There were no significant differences between (T2, T3, T4, T5, T6) compared with T1. The results indicate that the consumer accepted T2, T3, T4, and T5 treatments as well as T1. GC analysis showed the presence of phenolic compounds in mallow leaves powder, such as phenol, 2-chlorophenol, 2-methyl phenol, 4-methyl phenol, 2-nitrophenol, 2,4-dimethylphenol, benzoic acid, 2, 4- Dinitrophenol (0.150, 0.036, 0.03, 0.127, 1.360, 0.042, 0.002, 5.552 mg\100g) respectively.